2017
DOI: 10.1016/j.midw.2016.11.006
|View full text |Cite
|
Sign up to set email alerts
|

The economic costs of intrapartum care in Tower Hamlets: A comparison between the cost of birth in a freestanding midwifery unit and hospital for women at low risk of obstetric complications

Abstract: Objective To compare the economic costs of intrapartum maternity care in an inner city area for 'low risk' women opting to give birth in a freestanding midwifery unit compared with those who chose birth in hospital.Design Micro-costing of health service resources used in the intrapartum care of mothers and their babies during the period between admission and discharge, data extracted from clinical notes Setting The Barkantine Birth Centre, a freestanding midwifery unit and the Royal London Hospital's consultan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 11 publications
0
23
0
Order By: Relevance
“…In addition, an English study found that FMUs were cost-effective. 54 Chapter 2 Research approach and methods T his chapter details the research design and rationale for the methods of the three stages of the research. It describes the individual components of each stage, including a discussion of the theoretical underpinning for the analyses of the case studies.…”
Section: Updated Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, an English study found that FMUs were cost-effective. 54 Chapter 2 Research approach and methods T his chapter details the research design and rationale for the methods of the three stages of the research. It describes the individual components of each stage, including a discussion of the theoretical underpinning for the analyses of the case studies.…”
Section: Updated Literature Reviewmentioning
confidence: 99%
“…These rationales for closure were common, despite the extant scientific evidence that FMUs are as safe as hospital for babies and safer for mothers, 3 and that FMUs are the most cost-effective birthplace for low-risk women, even when occupancy is at an average rate of 30%. 46,54 They also failed to acknowledge the evidence that women are offered limited information 138 and that the choice to plan birth out of hospital is highly constrained by social norms. 158 One way of understanding the rationale for closures is that decision-making often takes place within managerial utilitarian frameworks, 156 which consider the directly observable local costs of buildings and staffing of FMUs, without including reference to corresponding savings in the acute service of, for example, theatre time or medical staffing.…”
Section: Rationale For Closuresmentioning
confidence: 99%
See 2 more Smart Citations
“…Midwifery units (commonly referred to as birth centres) have demonstrated improvements in maternal outcomes, transition to parenthood and satisfaction, and lower rates of intervention while maintaining neonatal outcomes equivalent to those on obstetric-led labour wards (Birthplace in England Collaborative Group, 2011;Macfarlane et al, 2014aMacfarlane et al, , 2014bOvergaard et al, 2012). They are also cost-effective (Schroeder et al, 2011(Schroeder et al, , 2017. For staff, midwifery units offer opportunities for midwives and doctors to become familiar with the physiological processes of birth, due to the high concentration of normal births which occur in these settings (Hodnett et al, 2012;Stone, 2012;Walsh and Devane, 2012).…”
Section: Introductionmentioning
confidence: 99%